Determinants of urban poverty in Petaling Jaya, Selangor - Mahadzir, Muhammad Syafiq; Ab Rani, Nor Zuriati Amani; Che Yaacob, Haslina; Husin, Suraya; Zahari, Nor Sabrina (Universiti Teknologi MARA, Kelantan, 2018)
Urban poverty, which is distinct from rural poverty due to demographic, economic and political aspects is still slightly in Selangor. This study have examined the determinants of urban poverty in Petaling Jaya, a part of a large-size city of Selangor. Although the incidence of poverty is decreasing in Selangor, there is still concerns about the urban poverty since the cost of living is rising. In addition, Selangor has raised its poverty income threshold from RM700 to RM1500 in 2015 [1] and the aftermath is worrying as it is estimated that about 30% of Selangor’s population will be classified as poor. The previous Asian financial crisis in 1997 had resulted in unemployment mainly in the manufacturing and construction will affect Selangor in terms of income as it has the biggest contributions in the sectors. This study was obtained using primary data consist of 100 households that live in urban area of Petaling Jaya, Selangor. The data analysed using Statistical Package for the Social Sciences software version 23.0 (SPSS 23.0). This study is in line with the plan in Eleventh Malaysia Plan (RMK-11) which is to increase the average household income of the Bottom 40(B40) group. Results of data found that an education level of household and age of household have significant relationship with household income while there is no significant relationship between household size and household income. It is recommended to have more variety of ways to attract more people to engage in higher education as a strategy for poverty reduction in urban area.